RESPON BEBERAPA VARIETAS BATANG ATAS DAN WARNA SUNGKUP PADA SAMBUNG PUCUK TANAMAN JERUK - Khansa Sulthanah Rumi; Fitri Yulianti; Muhammad Ridha Alfarabi Istiqlal; Paranita Asnur (Agroteknologi Fakultas Pertanian Universitas Islam Darul 'Ulum (UNISDA), 2024)
Citrus plants are a horticultural that is in great demand in various countries and has potential in the future, but still experiences problems in seedling propagation. Efforts to overcome this problem are grafting propagation. This study aims to determine the response of grafting results to the treatment of differences in scion varieties and cover colors and to determine the best grafting results between treatment combinations. The study was conducted in April-May 2022 in the Agrotechnology open land, Campus F7 Gunadarma University. The study was conducted with a randomized complete group design (rcbd) (4x4) with 3 replications. The first factor is the difference in scion varieties (nipis, limo, pamelo, and sunkist), the second factor is the cover color (red, yellow, blue and transparent). The results showed that the success of grafting based on the highest scion variety was obtained in the limo and pamelo varieties of oranges, while for cover colors it was obtained in transparent and yellow colors, the treatment of scion varieties had a significant effect on the variables of scion height, scion diameter, number of shoots and number of leaves. Meanwhile, the color treatment of the cover had a significant effect on the variables of plant height and upper stem height.